Mobilizing health district management teams through digital tools: Lessons from the District.Team initiative in Benin and Guinea using an action research methodology - Basile Keugoung; Kéfilath Olatoyossi Akankè Bello; Tamba Mina Millimouno; Sidikiba Sidibé; Jean Paul Dossou; Alexandre Delamou; Antoine Legrand; Pierre Massat; Nimer Ortuno Gutierrez; Bruno Meessen (Wiley, 2021)
Abstract Background Improving capacities of health systems to quickly respond to emerging health issues, requires a health information system (HIS) that facilitates evidence‐informed decision‐making at the operational level. In many sub‐Saharan African countries, HIS are mostly designed to feed decision‐making purposes at the central level with limited feedback and capabilities to take action from data at the operational level. This article presents the case of an eHealth innovation designed to capacitate health district management teams (HDMTs) through participatory evidence production and peer‐to‐peer exchange. Methods We used an action research design to develop the eHealth initiative called "District.Team," a web‐based and facilitated platform targeting HDMTs that was tested in Benin and Guinea from January 2016 to September 2017. On District.Team, rounds of knowledge sharing processes were organized into cycles of five steps. Quantitative and qualitative data were collected to assess the participation of HDMTs and identify enablers and barriers of using District.Team. Results Participation of HDMTs in District.Team varied between cycles and steps. In Benin, 79% to 94% of HDMTs filled in the online questionnaire per cycle compared to 61% to 100% in Guinea per cycle. In Benin, 26% to 41% of HDMTs shared a commentary on the results published on the platform while 21% to 47% participated in the online discussion forum. In Guinea, only 3% to 8% of HDMTs shared a commentary on the results published on the platform while 8% to 74% participated in the online discussion forum. Five groups of factors affected the participation: characteristics of the digital tools, the quality of the facilitation, profile of participants, shared content and data, and finally support from health authorities. Conclusion District.Team has shown that knowledge management platforms and processes valuing horizontal knowledge sharing among peers at the decentralized level of health systems are feasible in limited resource settings.